Knowledge, attitude and practices of patients’ relatives about cancer: a study from Eastern India - Paul, Rudrajit; Sinha, Sourav; Asifullah, Md.; Mallick, Swapan K.; Mondal, Jayati (International Journal Of Community Medicine And Public Health, 2017)
Background: Knowledge, attitude and practice (KAP) about a disease can significantly affect healthcare seeking behaviour and thus, ultimate outcome of a disease. This is particularly true in chronic diseases like cancer. In India, the influence of family members on the treatment decision of an individual is paramount. Hence, KAP of the family about a disease will significantly affect the healthcare pathway of any individual. However, actual data on KAP of common people about cancer are very rare from India. In this Eastern Indian study, we aimed to generate data on this very important aspect. Methods: In this hospital based study, the relatives of cancer patients were interviewed about their perception about various aspects of cancer. The interview was based on a pre-structured questionnaire modelled after the “Illness Perception Questionnaire”. Results: We had 65 subjects in our study with a mean age of 43.5 years. 32% of the subjects belonged to some profession related to medicine. 44.6% of the subjects thought that cancer was synonymous with tumour. The chief source of information for our respondents was their physician only. Only 5% got their information about cancer from the mass media. The relationship between tobacco and cancer was known to a significant fraction with 21.5% responding that smoking causes cancer and a further 18.5% knowing about other tobacco products as the cause. More than 1/4th of the subjects thought that any cancer was a permanent disease. Most (71%) study subjects thought that living with a cancer patient was difficult. 32% believed that cancer meant inevitable death. Almost 2 out of every 5 had used some form of alternative medicine therapy for cancer. Subjects with lower educational status were statistically more likely to use alternative medicine. Regarding the prevention of cancer also, opinions varied widely according to educational level with almost 70% of the subjects in the illiterate subset opining that cancer is non-preventable. Conclusions: This study shows that the perception about cancer varied widely in the society according to various factors like educational level and/or gender. A significant number of subjects had personal outlook which was quite different from current scientific data. Hence, proper dissemination of information about diseases like cancer in the society is an important need of the hour.